Comparison of soil erosion under no-till and conventional tillage systems in the high rainfall Mlondozi area, Mpumalanga province, South Africa - Barnard, R.O. (Robin Oxley), 1940- (University of Pretoria, 2015)
Dissertation MInst (Agrar)--University of Pretoria, 2014